Okapande: Pendekatan Heutagogi dalam Kearifan Lokal Masyarakat Muna di Sulawesi Tenggara - Syahrun; Aswati M; Winesty S, Wa Ode; Burhan, Faika; Hasan, Hasni (Prosiding Seminar Nasional Fakultas Tarbiyah dan Ilmu Keguruan IAIM Sinjai, 2023)
The heutagogy learning method is effective and efficient for improving the learning process. The onslaught of globalization and the era of society 5.0 has its challenges. This method is expected to be able to foster a sense of interconnectedness between not only teachers and students but also involves local wisdom amid society. There is a need for local knowledge that can improve welfare and create peace. The aim of the heutagogy learning method in okapande is a learning component based on the local wisdom of the Muna people. Okapande provides its dimension in terms of modern learning and can foster cultural values in the Muna community. Local wisdom that exists amid society can be a source of forming national character. The existence of local wisdom is an ancestral heritage that contains values and norms as character builders. Learning is not only to increase knowledge but also to make people wiser. Okapande, which is a learning media, not only emphasizes knowledge but closeness to God. This research was qualitative research with the use of a literature study. The study results show that the heutagogy learning method can provide skills to communicate, adapt, collaborate, and play a role in the human characteristics forming process.